Standard operating procedure (SOP) of building dilapidation survey / Muhammad Syafiq Mohd Kamil - Mohd Kamil, Muhammad Syafiq (Universiti Teknologi Mara, Perak, 2017)
Dilapidation Survey is also known as a pre-construction condition survey in Malaysia (or sometimes called structural survey). A dilapidation survey done by a Professional Building Surveyor is an inspection of the existing structural condition of of the surrounding buildings and structures before the commencement of a demolition, construction or development. All prominent defects in the form of cracks, settlement, movement, water seepage, spalling concrete, distortion, subsidence and other building defects will be recorded in photographs together with notes. For the case study of this report, the Chengal Jati Sdn Bhd is a main contractor for New Proposed Elevated Highway Sg Besi – Ulu Kelang (SUKE) Package CA 1. Jasa Sendi (M) Sdn Bhd is a sub-contractor hired by the Chengal Jati Sdn Bhd to carry out the dilapidation survey works. The purpose of building dilapidation is to identify and record any defects or damages that already occurred in existing building within the 50 metre from the construction site.